2014
DOI: 10.1007/s12032-014-0387-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β-mediated suppression of microRNA-101 and upregulation of enhancer of zeste homolog 2 is involved in particle-induced lung cancer

Abstract: Lung cancer may be a result of complex factors. Small mineral particle is the well-known inducer of lung cancer. Previous study revealed the high morbidity of lung cancer in Xuan Wei in China, and the main cause of lung cancer is the use of smoky coal there. And it is generally accepted that chronic inflammation induced by small mineral particle may be a cause of lung cancer. But the relationship between chronic lung inflammation and lung cancer is largely unknown. In the present study, we found that silica pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It has been reported that miR-101 inhibits cell proliferation and invasion of lung cancer by regulating cyclooxygenase-2 ( 35 ). Additionally, low expression of miR-101 in lung cancer has been demonstrated to inhibit the invasion of lung cancer by regulating its target gene enhancer of zerte 2 polycomb repressive complex 2 subunit ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-101 inhibits cell proliferation and invasion of lung cancer by regulating cyclooxygenase-2 ( 35 ). Additionally, low expression of miR-101 in lung cancer has been demonstrated to inhibit the invasion of lung cancer by regulating its target gene enhancer of zerte 2 polycomb repressive complex 2 subunit ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-101 is a miRNA that regulates a variety of tumor-related biological processes by modulating the expression of several target genes at the transcript or protein level (25,26). Normally, miR-101 inhibits the expression of lung cancer promoting genes (17,27). In this study, we observed a miR-101 binding site at 3891–3912 nt of the DNMT3A 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring the molecular and cellular mechanisms of lung cancer is important. Early screening strategies can be developed, and deciphering the mechanism underlying tumorigenesis may facilitate the development of new strategies to successfully treat cancer and cancer-associated diseases (23). …”
Section: Discussionmentioning
confidence: 99%